A comparative study of two nanosubstrates for the on-line solid phase extraction of antimony by FI-HG-AAS - Londonio, Juan Agustín (2016)
Nanoporous carbon (NPC) prepared frommetal organic frameworks (MOFs)was studied to serve as a sorbent forpreconcentrating Sb(III) at trace levels. The performance of NPC regarding sensitivity, enrichment factor, analyticalthroughput and recovery was compared with that of multiwalled carbon nanotubes functionalised with Lproline(pro-MWCNTs). In this study, Sb(III)was preconcentrated using both substrates using an on-line flow injectionhydride generation atomic absorption spectrometry (FI-HG-AAS) system. A low molecular weight polyethylenewas added to the sorbent material to fill the preconcentration columns to avoid nanoparticleaggregation. A comprehensive study of the type and concentration of the reactionmedia and the eluentwas carriedout to select the best substrate not only in terms of adsorption capacity but also considering potentialinterferent control. The study evidenced that for Sb(III) retention, phtalate buffers (1.0 mM at pH=6) resultedthe best alternative. Under optimal conditions, both substrates exhibited high adsorption capacities:343 mg Sb g−1 NPC and 559 mg Sb g−1 pro-MWCNTs. The preconcentration factors reached were: 258 and420 for NPC and pro-MWCNTs, respectively. The high adsorption capacity of both substrate allowed reaching detectionlimits (3σ) of 1.47 and 0.52 ng L−1 for NPC and pro-MWCNTs, respectivelywhen using a sorbent columncontaining only 1.0 mg of sorbent. Precision, expressed as relative standard deviation (RSD) turned to be ~2% atthe 0.1 μg L−1 level (n=10) for both substrates. Trueness test for the entire analytical procedurewas performedby means of the Standard Reference Material (SRM) NIST 1643e (Trace elements in water) and results were ingood agreement with the certified values. The system was evaluated for quantitative determination of Sb(III)in different kind of waters. The method is simple and relatively cheap in comparison with other methodologies.